ASSESSMENT METHODS OF CONFORMITY WITH UNCTIONAL AIRCRAFT SYSTEMS TO AIRWORTHINESS REQUIREMENTS - I. D. Dashkov (Научный вестник МГТУ ГА, 2016)
This article discusses issues related to the conformity assessment of functional systems of aircraft to airworthiness requirements of aircraft, provides a detailed analysis of each of them, as well as considers their effectiveness during the operational phase.